A Solution for Creating the Simulating Load on Connecting-Rod in the Experimental Device for Lubricating Condiction of the Connecting-Rod Big End Bearing - Tran, Thi Thanh Hai (Old Journal, 2018)
The longevity and reliability of the crankshaft-connecting rod assembly in internal combustion engines depends very much on the lubricated regime. Connecting-rod is an important part of the engine, in which the connecting-rod big end bearing works in severe conditions (heavy load and dynamic, high velocity, high temperature, ...). The calculation research for this type bearing need always be equipped with experimental device to compare the calculated results and the experimental results. This paper presents the load simulation solution corresponding to the engine's operating cycle and the force measurement method applied to connecting-rod (connecting-rod big end) model of photoelastic in the special device for lubricating of the connecting-rod big end bearing. The force acting on the connecting-rod includes two traction/compression and flexion forces. These forces are measured by strain gauges by the installation of bridge sensors.).